2020
DOI: 10.1111/aec.12854
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of dasyurid marsupials in dryland Australia: Variation across habitat and time

Abstract: The irruptive population dynamics of rodents are a globally renowned wildlife phenomenon; however, the dynamics of other small mammals with which rodents are sympatric are poorly understood. Dryland Australia supports a high diversity of small (<200 g) arthropod-eating marsupials (Dasyuridae). Here, we test the hypothesis that dasyurid marsupials do not exhibit the same degree of irruptive population dynamics that are shown by rodents. We addressed this question by sampling small mammal assemblages on 20 perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Yet longitudinal studies of desert marsupial insectivores have revealed their abundance is not strongly tied to rainfall (Pavey et al . 2020), unlike that found for rodents (Greenville et al . 2016).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Yet longitudinal studies of desert marsupial insectivores have revealed their abundance is not strongly tied to rainfall (Pavey et al . 2020), unlike that found for rodents (Greenville et al . 2016).…”
Section: Discussionmentioning
confidence: 65%
“…This relationship was unexpected given that the Pilliga is a dry forest, and we suspected drought conditions and associated effects on productivity, as measured by NDVI, would be more important (Watson 2011;Rodhouse et al 2015). Yet longitudinal studies of desert marsupial insectivores have revealed their abundance is not strongly tied to rainfall (Pavey et al 2020), unlike that found for rodents (Greenville et al 2016). Instead, Pavey et al (2020) suggested that the ability of dasyurids to enter torpor to save energy may decouple population dynamics from rainfall-driven primary productivity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous research has also suggested that small to medium dasyurids may be unable to rapidly respond and take advantage of increased resource availability or improved environmental conditions (Dickman et al, 2001). Longer-term monitoring has shown that small to medium dasyurids display a delayed response to large rainfall events (Pavey et al, 2020) and small dasyurids respond to the larger dasyurid predator, the mulgara, rather than invasive predators, such as feral cats and foxes (Greenville et al, 2017). In contrast, Pedler et al (2016) found a substantial increase in the distribution of the crest-tailed mulgara (Dasycercus cristicauda) following a rabbit haemorrhagic disease virus (RHDV) outbreak that suppressed rabbit populations and consequently reduced feral cat and fox numbers.…”
Section: Discussionmentioning
confidence: 99%